FAKTOR-FAKTOR YANG MEMPENGARUHI KEMATIAN IBU DI KABUPATEN BANYUMAS JAWA TENGAH PERIODE TAHUN 2009-2011 - ., Sumarni (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
Maternal Mortality Rate ( MMR ) is one indicator of health status . These factors , among others ; anemia , diseases , antenatal care , obstetric history , family economics , education . Banyumas is one of the 5 districts with a value more than the value of AKI AKI province . This study aims to determine the factors that influence maternal mortality in Banyumas district in 2009-2011. This study uses Mixed Methods . Qualitative study using Sequential Explanatory Designs strategies , whereas quantitative study with case-control . The experiment was conducted in a hospital in Banyumas district . The population of this study were all cases of obstetric referral hospital in Banyumas district in 2009-2011. Qualitative and quantitative sampling techniques each uses total sampling and purposive sampling . Quantitative samples in this study amounted to 206 samples consisting of 103 cases and 103 control samples and sample groups totaling 17 inforaman qualitative . Analysis of data using multiple logistic regression . While qualitative analysis using the theory of interpretation. The results showed that the disease , occupation , history of antenatal care and referral to maternal mortality has a significant relationship with maternal mortality ( p = 0.018 ; OR = 2.42 ( 1.16 to 5.02 ) , p = 0.019 ; OR = 3 , 49 ( 1.22 to 9.95 ) , p = 0.007 ; OR = 5.15 ( 1.57 to 16.93 ) , p = < 0.001 ; OR = 4.49 ( 2.30 to 8.78 ) , whereas anemia , occupation , education , age and obstetric history no association with maternal mortality . factor antenatal care is the most dominant factors affect maternal mortality , OR 5.15 ( 1.57 to 16.93 ). quantitative analysis of the results obtained factors that cause results antenatal care becomes the dominant cause for the lack of public knowledge on obstetric complications , late referral , less concerned for the family of the mother during pregnancy concerns , a lack of communication between health workers in detecting complications of pregnant women. Keywords : factors, maternal mortality